Crystallization ages of Paleoproterozoic A-type granites of Carajás province, Amazon craton: Constraints from U-Pb geochronology of zircon and titanite - Barbosa Teixeira, M.; Dall'Agnol, R.; Schneider Santos, J.; Carvalho de Oliveira, D.; Lamarão, C.; McNaughton, Neal (Pergamon, 2018)
New U-Pb SHRIMP dating in zircon and titanite showed that the three large Paleoproterozoic A-type granite Suites and related granites from Carajás Province of the Amazon Craton (Brazil) were emplaced between 1880 Ma and 1857 Ma, with the main magmatic peak at 1880 Ma. Some particular ages not reported before have been identified: (i) ages of 1865 Ma to 1857 Ma in leucogranite facies of the Redenção and Bannach plutons, that are younger, were generated by independent magma pulses and are not cogenetic with the dominant ~1880 Ma old granites of the respective plutons; (ii) an age of 1732 ± 6 Ma obtained in the leucogranite facies of the Antônio Vicente pluton of the Velho Guilherme Suite that could represent a magmatic event in the Xingu Region not yet reported or, eventually, could correspond to an isolate hydrothermal event that allowed the growth of zircons. The more detailed geochronological data obtained in the Paleoproteozoic A-type granites of Carajás Province, added to the information available in the literature, demonstrate the relevance of the magmatic event at ~1880 Ma and indicate that the emplacement of those granites was done in about ~20 m.y. that means in a relatively short geological time. This 1880 Ma magmatic episode was also intense in other provinces of the Amazon Craton, where it is linked mostly to the formation of the Uatumã Silicic Large Igneous Province. This event was mostly extensional and isalso registered in several cratons worldwide demonstrating its relevance in the tectonic evolution of Proterozoic continents.